A thyrotoxicosis outbreak due to dietary pills in Paris - Vincent Ioos; Vincent Das; Eric Maury; Jean-Luc Baudel; Jérôme Guéchot; et al (Dove Medical Press, 2008)
Vincent Ioos1, Vincent Das1, Eric Maury1,2, Jean-Luc Baudel1, Jérôme Guéchot3, Bertrand Guidet1,2, Georges Offenstadt1,21Réanimation Médicale; 2Université Pierre et Marie Curie-Paris 6, INSERM, UMR-S 707; 3Unité d’Hormonologie, APHP, Hôpital Saint Antoine, F-75012, Paris, FranceAbstract: Three women were consecutively admitted to our medical intensive care unit for thyrotoxicosis after the ingestion of dietary pills accidentally containing high levels of thyroxin. These cases were observed during an outbreak in the Paris area. Despite similar blood levels of thyroid hormones, their clinical presentation and outcome were very different. One patient developed febrile confusion and died from malignant hyperthermia. The second one had progressive confusion requiring mechanical plasma exchange therapy and had a favorable outcome. The third one had very moderate symptoms. These exceptional observations raise several issues concerning diagnosis, physiopathology and treatment of thyrotoxicosis factitia.Keywords: thyrotoxicosis, dietary pills, thyroxin